Accuracy Score on Raja Isteri Pengiran Anak Saleha (RIPASA) and Pediatric Appendicitis (PAS) for Diagnosing Acute Appendicitis in Children - M. Roby; Shalita Dastamuar; Sindu Saksono; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Introduction. Acute appendicitis is the most common case of acute abdomen. Diagnosis of acute appendicitis is still difficult and is one of the problems in the surgical field. The Clinical Scoring System (CSS) has been developed to help doctors classify risk categories. PAS has been widely evaluated in the pediatric population. In another study it was found that RIPASA had better sensitivity, specificity, and accuracy than PAS in pediatric patients. Methods. This study is a cross sectional study to assess the level of concordance between RIPASA and PAS scores in diagnosing acute appendicitis, with the gold standard of Histopathological examination. Samples were taken by consecutive method, in 30 patients aged <18 years for 1 year. Results. This study had an average age of 10.10 Â± 3.745 years. Histopathologically early acute appendicitis 3.3%, acute suppurative appendicitis as much as 20%, acute gangrenous appendicitis 73.3% and others 3.3%. Using a cut-off point value of 9.5 for RIPASA and 7 for PAS, the sensitivity, Specificity, Accuracy of 82.75%, 100%, 80% for RIPASA, and 75.8%, 100%, 73.3% for PAS. Conclusion. The RIPASA score on the cut-off treshold 9.5 has better sensitivity and accuracy than PAS in diagnosing acute appendicitis in pediatric patients and can be used as CSS to assist in making decisions regarding the diagnosis of acute appendicitis in children.